Formation of the Civic-Patriotic and Cultural Identity of Students in the Context of the Expansion of the Unified Educational Space of the Russian Federation - Svetlana A. Kochetova; Svetlana E. Ziabreva (Вестник Московского Университета. Серия 20: Педагогическое образование)
Background. The article covers the issue of patriotism in educating young people as a priority state task. Education of a patriot, the formation of the Russian civil-patriotic identity of the younger generation is a matter of national security today. In a special way, this issue becomes in demand when it comes to the training and education of future teachers.